Survei Sikap Dalam Pembelajaran Pjok Pada Siswa SMK Negeri 4 Buru - Dewi Sagita Balun; Jacob Anaktototy; Siti Divinubun (Jurnal Ilmiah Wahana Pendidikan, 2023)
The variable in this research is a single variable, namely the Survey of Attitudes in Corner Learning for Students at SMK Negeri 4 Buru in participating in physical education. What is meant in this research is a person's tendency to behave, desire, and persevere or encourage them to take physical education lessons at school. The data collection technique in this research is to use a questionnaire to collect survey data on interest in learning physical education. Questionnaires are circulated individually in order to control respondents to fill out questionnaires so that the data obtained is data that is filled in correctly by respondents without being influenced by other people or friends. Data obtained from research results regarding interest in learning physical education among students in the Survey of Attitudes in Learning Physical Education among Students at SMK Negeri 4 Buru. Data analysis in this research uses percentage descriptive statistical analysis. This research data is categorized into five (5) categories, namely; strongly disagree (1), disagree (2), disagree (3), agree (4), and strongly agree (5). The results of descriptive statistical analysis of overall PJOK interest in learning data obtained the lowest score (Min) = 68; highest score (Max) = 116; Mean (M) = 99. In more detail, scores and categories of interest in learning PJOK.